Program Rumah Asa: Harapan untuk Mereka yang Terlantar - Lianah The; Andy, Andy; Jeni Harianto; Duha, Delfina Wahyu; Ariswana, Aan Novisga; Syahrudin, Ardian (Pusat Riset dan Inovasi Nasional, 2026)
This research was conducted to describe the condition of displaced communities who experience limitations in meeting basic needs, such as decent housing, access to education, and health services. Socio-economic inequality is the main factor that affects the quality of life of vulnerable groups, including children, adults, and the elderly. The Rumah Asa program is designed as an effort to provide protection, psychological support, and economic empowerment through skills training and health services according to needs. The research used a qualitative approach through interviews, field observations, and questionnaire dissemination to gain an in-depth understanding of the respondents' living situation. The research population consisted of displaced individuals who had the potential to become beneficiaries of the program. The data obtained were analyzed to identify patterns of vulnerability and intervention needs. The results showed that each respondent faced unstable socio-economic conditions, with limited income, lack of family support, and high health risks. The discussion showed that neglect is multidimensional and requires comprehensive interventions that include material, emotional, social, and health aspects. The conclusion of the study confirms that the Rumah Asa Program has great potential as a model of effective social intervention in improving the quality of life of vulnerable groups, as long as it is supported by the collaboration of the community, government, and social institutions.